IgE Production to α-Gal Is Accompanied by Elevated Levels of Specific IgG1 Antibodies and Low Amounts of IgE to Blood Group B - Rispens, Theo (Public Library of Science, 2013)
IgE antibodies to gal-α-1,3-gal-β-1,4-GlcNAc (α-gal) can mediate a novel form of delayed anaphylaxis to red meat. Although IgG antibodies to α-gal (anti-α-gal or anti-Gal) are widely expressed in humans, IgE anti-α-gal is not. We explored the relationship between the IgG and IgE responses to both α-gal and the related blood group B antigen. Contradicting previous reports, antibodies to α-gal were found to be significantly less abundant in individuals with blood group B or AB. Importantly, we established a connection between IgE and IgG responses to α-gal: elevated titers of IgG anti-α-gal were found in IgE-positive subjects. In particular, proportionally more IgG1 anti-α-gal was found in IgE-positive subjects against a background of IgG2 production specific for α-gal. Thus, two types of immune response to α-gal epitopes can be distinguished: a ‘typical’ IgG2 response, presumably in response to gut bacteria, and an ‘atypical’, Th2-like response leading to IgG1 and IgE in addition to IgG2. These results suggest that IgE to a carbohydrate antigen can be formed (probably as part of a glycoprotein or glycolipid) even against a background of bacterial immune stimulation with essentially the same antigen.